Pendampingan Peningkatan Kompetensi Komunikasi Bahasa Inggris Pegawai Basarnas Melalui English One Day Di Basarnas Makassar - Yahrif, Muhammad; Dhaniar; Arie Pratama Putra (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
English competency assistance is one of the main things that a worker must have. The ability to speak English is a basic skill that a person needs in this era of globalization related to the introduction and mastery of science and technology. However, based on the results of observations made at Basarnas Makassar, the English language competency of several employees is still very minimal. The knowledge possessed by human resources in the office is the main factor in the use of English which is still very minimal, and many employees even think that learning English is still not an important thing in employees' careers and duties. Based on these findings, it is very necessary to provide support for the English language competency of Basarnas employees through English language teaching in the office. This community service uses descriptive methods. Based on the results of feedback from this PKM activity, the majority of training participants felt positive things about themselves starting to be confident in using English. So it can be concluded that this PKM activity is going well.